Christian education and political education for Christians in Indonesia - Mau, Marthen (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
The problem that usually occurs is that some political people consider it dirty, unclean, unclean, evil, and sinful, but that opinion is not true. Usually, unscrupulous politicians abuse their authority in politics for the benefit of themselves, their families, and groups, thus ignoring the public interest. Therefore, the purpose of this research is to encourage Christian educators to teach Christian education and political education for the benefit of the general public; as well as to open the horizons of thinking for Christians and the public as a whole. This paper uses qualitative methods through literature studies to produce an understanding of Christian and political education correctly so that it can make everyone happy. So, the results found are that if Christian educators are increasingly loyal to teaching Christian education and political education in the right way, then everyone who is taught will continue to do the right thing too.